A new methodology to extend the validity of the Hargreaves-Samani model to estimate global solar radiation in different climates: Case study Mexico. (December 2017) - Rivero, M.; Orozco, S.; Sellschopp, F.S.; Loera-Palomo, R.
Abstract: This work presents a modification to the model proposed by Hargreaves and Samani, based on daily temperature difference, to estimate daily global solar radiation. This is done by analyzing the relation between daily temperature increments and the fitting parameter in the model. Six different climates and four day types have been considered. Day classification was done in accordance to the daily clearness index. The proposed model was validated on a database that comprises 47 stations distributed in Mexico. The proposed methodology to estimate daily solar global radiation is compared against the original Hargreaves model, using fixed reported values for the fitting parameter. The performance of the proposed model is done based on four metrics commonly used. The proposed model reduces the overall errors and bias from the original model, and thus its validity on different climate types is extended. It was obtained a reduction of the RMSE of at least 15% and up to 30%, depending on climate, when compared with the Hargreaves-Samani model. Obtained RMSE are below the mean RMSE reported in literature. Similar improvements were observed with other metrics. In addition, average daily clearness index for each station and their distribution are presented for all stations.